∫(e^xdx)/√(1-e^2x)=?
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 16:40:01
∫(e^xdx)/√(1-e^2x)=?∫(e^xdx)/√(1-e^2x)=?∫(e^xdx)/√(1-e^2x)=?令e^x=t,x=lnt,dx=1/tdt∫e^x/√(1-e^2x)dx=∫[
∫(e^xdx)/√(1-e^2x)=?
∫(e^xdx)/√(1-e^2x)=?
∫(e^xdx)/√(1-e^2x)=?
令e^x=t,x=lnt,dx=1/tdt
∫e^x/√(1-e^2x)dx
=∫[t/√(1-t²)]•(1/t)dt
=∫1/√(1-t)²dt
=arcsint+C
=arcsine^x+C
∫1/√(1-t)²dt这样的用三角代换我跟你说了很多了,这里就不详细写了啊
∫(e^xdx)/√(1-e^2x)=?
∫e^xdx/[e^(2x)-1]
∫ (x+1)e^xdx=?
∫ (x^2+1)e^xdx
∫(x^2+1)e^xdx
∫(x+1)e^xdx
∫x^2/e^xdx
∫ e^(-x^2)xdx
∫e^x^2*xdx
∫x^2e^xdx
∫[e^(-x)]/xdx.
∫e^x√3-2e^xdx不定积分
积分∫0 +∞e^xdx/e^2x+1
∫e^2x/1+e^xdx=∫e^x/e^xde^ex这步怎么化的?
求不定积分 ∫e^2xdx/[(e^4x)+4] ∫lnxdx/x√(1+lnx)
∫(x^2+x-2)e^xdx
求∫x²e^xdx=
∫(1→∞)x/e^xdx